Molecular mechanisms of action of systemic lidocaine in acute and chronic pain: a narrative review. (September 2019) - Hermanns, Henning; Hollmann, Markus W.; Stevens, Markus F.; Lirk, Philipp; Brandenburger, Timo; Piegeler, Tobias; Werdehausen, Robert
Summary: Systemic administration of the local anaesthetic lidocaine is antinociceptive in both acute and chronic pain states, especially in acute postoperative and chronic neuropathic pain. These effects cannot be explained by its voltage-gated sodium channel blocking properties alone, but the responsible mechanisms are still elusive. This narrative review focuses on available experimental evidence of the molecular mechanisms by which systemic lidocaine exerts its clinically documented analgesic effects. These include effects on the peripheral nervous system and CNS, where lidocaine acts via silencing ectopic discharges, suppression of inflammatory processes, and modulation of inhibitory and excitatory neurotransmission. We highlight promising objectives for future research to further unravel these antinociceptive mechanisms, which subsequently may facilitate the development of new analgesic strategies and therapies for acute and chronic pain.